Research in personnel and human resources management. Vol. 37 - Buckley, M. Ronald; Wheeler, Anthony R.; Baur, John E.; Halbesleben, Jonathon R. B. (Emerald Publishing Limited, 2019)
Volume 37 of Research in Personnel and Human Resources Management contains six original scholarly monographs written by thought leaders in the field of human resources management. This volume focuses on human resources branding, innovation and creativity in human resources management, high involvement work systems, work home boundary permeability, the emerging concept of grit in human resources management, and data visualization issues in human resources management.
Keywords: Personnel management.; Business & Economics -- Human Resources & Personnel Management.; Personnel & human resources management.; elektronické knihy; electronic books